Эмиграция евреев в контексте общей миграционной ситуации в Украине - Шульга, Н.; Панина, Н.; Головаха, Е.; Зисельс, И. (Социология: теория, методы, маркетинг, 2001)
In the article, there are analyzed development tendencies, current situation and
prospects of Jewish emigration within the general migratory situation in Ukraine. The
empirical research is based on the official statistics data of Ukraine, Israel, USA and
Germany, as well as the polling data related to migratory plans and departure of Jews
from Ukraine. The authors argue that current emigration range and tempos are
determined mostly by economic factors. There are described the tendencies and
structural specific features of Jewish emigration, its ethnic and socio-demographic
parameters. There are also studied some aspects of adaptation in new places and
problems of illegal migration. The prognosis on further development of migratory
processes and prospects of Jewish minority in Ukraine are regarded too.